2006
DOI: 10.1016/j.euje.2005.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial stiffness and the timing difference between tissue Doppler imaging Ea and peak mitral valve opening can distinguish physiological hypertrophy in athletes from hypertrophic cardiomyopathy

Abstract: Physiological hypertrophy can be differentiated from hypertrophic cardiomyopathy in athletes using the Ea-peak mitral opening difference, and our index of ventricular stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
2
12
0
1
Order By: Relevance
“…Considering these facts it is logical that endurance component in training by consequent LV enlargement reduces chamber stiffness, and this was demonstrated by previous studies 5,11–14 . But, using this logic in a condition of increased wall stress, low LVV and increased LVM, which characterize strength training, chamber stiffness should be increased 12,45 …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Considering these facts it is logical that endurance component in training by consequent LV enlargement reduces chamber stiffness, and this was demonstrated by previous studies 5,11–14 . But, using this logic in a condition of increased wall stress, low LVV and increased LVM, which characterize strength training, chamber stiffness should be increased 12,45 …”
Section: Discussionmentioning
confidence: 95%
“…In a condition of increased demand, when the heart is influenced by hemodynamic load and neurohumoral activation, it undergoes changes of systolic function and relaxation, as well as changes of passive properties of the left ventricle when the myocardium is fully relaxed, which affects chamber stiffness 4 . Alteration of chamber stiffness might be an early sign of myocardial pathological changes 5 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They have been shown to be independent of haemodynamic loading conditions and a more robust method of assessing diastolic function. We have previously demonstrated that the stiffness index can differentiate physiological from pathological LVH by the presence of increased LV stiffness and reduced compliance 4. In the study by Spirito et al incorporating 947 elite athletes representing 27 different sports, rowing was ranked first in the likelihood of training-induced increase in LV wall thickness and seventh in the likelihood of training-induced increase in LV cavity size 2.…”
Section: Discussionmentioning
confidence: 99%
“…Pulsed‐wave tissue Doppler imaging (TDI) velocities were assessed at 4 conventional sites around the mitral annulus in the apical four and two‐chamber views, and averaged to give myocardial peak systolic (Sm) and peak early (Em) diastolic velocities. We assessed LV diastolic stiffness using an index we have previously reported, as the ratio of (E/Em)/LV end‐diastolic diameter . Right ventricular (RV) size was determined by the mid‐RV cavity diameter in the apical four‐chamber view, and RV free wall thickness from the apical and subcostal four‐chamber views.…”
Section: Methodsmentioning
confidence: 99%